2023
DOI: 10.1177/10755470231199955
|View full text |Cite
|
Sign up to set email alerts
|

Minoritized Scientists in the United States: An Identity Perspective to Science Communication

Leilane Rodrigues,
Bruno Takahashi,
Leigh Anne Tiffany
et al.

Abstract: This study investigates how tenure-track faculty from historically marginalized groups in the environmental sciences approach science communication based on their self-identities. A thematic analysis of 28 in-depth interviews with U.S.-based participants using the Communication Theory of Identity and Border-Crossing Theory was conducted to explore the interrelation of layers of identity, the identity gaps participants experience, and their communication practices. The results show that communication merges fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…The analysis of self-identifications of identities from 712 workshop participants revealed a diverse range of intersectional identities. These results align with current research findings from Rodrigues et al [2023], where research scientists from BIPOC backgrounds saw their identities as fluid, layered, and complex.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The analysis of self-identifications of identities from 712 workshop participants revealed a diverse range of intersectional identities. These results align with current research findings from Rodrigues et al [2023], where research scientists from BIPOC backgrounds saw their identities as fluid, layered, and complex.…”
Section: Resultssupporting
confidence: 88%
“…These frames can interact and overlap, influencing how a person forms their identity. Rodrigues, Takahashi, Tiffany, Menezes and Valdéz-Ward [2023] found that communication integrates various aspects of identity, fostering a dynamic awareness of self and communication style rather than a fixed self-concept. The results of the study by Rodrigues et al [2023], underscore a gap in most science communication training programs, including both short-term skills-based training [Baram-Tsabari & Lewenstein, 2017] and longer fellowships [Bennett et al, 2022;Roca, Coleman, Haelle & Lee, 2020], where full integration of participants' identities for culturally responsive training is often lacking.…”
Section: Stem Identitymentioning
confidence: 99%
See 1 more Smart Citation